Characterization of bending vibration fatigue of WBD fabricated Ti-6Al-4V. (August 2017) - Ellyson, Benjamin; Chekir, Nejib; Brochu, Mathieu; Brochu, Myriam
Highlights: Vibratory fatigue of WBD Ti-6Al-4V for two build directions and deposition speeds. Mean and spread of failure probability distribution at 10 7 cycles determined. Defect-free fatigue crack initiation mechanisms identified. Abstract: Wire Beam Deposition (WBD) is an Additive Manufacturing (AM) technique used in creating thick or thin geometries from wire stock. This technique has recently generated interest in the aerospace field for its potential to fabricate high performance, defect-free materials while minimizing post-processing and achieving high buy-to-fly ratios. Also, vibration fatigue is a technique used to generate fatigue data representative of turbine blade and vane High Cycle Fatigue (HCF) failure conditions. In this work, cantilever vibration bending fatigue of Ti-6Al-4V produced by WBD is studied. Tensile strength results are also briefly presented. Specifically, the Failure Probability Distribution (FPD) for 10 7 cycles is quantified using the Dixon-Mood staircase method. Additionally, fractography and microstructure data are used to supplement fatigue results and understand the failure mechanisms of the studied material states. Lastly, SLM fatigue and 3D vibrometry data are used to perform a comparative analysis of vibration fatigue performance of these two AM processes. The study finds that high deposition speeds lead to high fatigue performance. The material deposited at 454.66 mm/min had a performance nearly isotropic in nature and surpassing that of the reference material (AMS 4911). It was also found that WBD produced Ti-6Al-4V has a slightly lower crack nucleation resistance than the best-case SLM material, while showing a narrower spread for failure probability.